Optimization of the Role of Lawyers in Debt Restructuring and PKPU in Indonesia: A Juridical Study on the Protection of Debtors and Creditors - Vidya Ayuningtyas; Clarisa Clarisa; Novita Rahmawati; Albertus Satrio; Kristanta Kristanta; Luthfian Hananta; Anggo Doyoharjo (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
Debt restructuring and Suspension of Debt Payment Obligations (PKPU) are legal instruments in the Indonesian bankruptcy system aimed at providing legal protection and maintaining a balance of interests between debtors and creditors. In practice, the PKPU process is not only related to the settlement of debts but also involves business continuity, legal certainty, and the stability of the business world. This research aims to analyze the position and optimization of the role of advocates in debt restructuring and the PKPU process in Indonesia, as well as to examine their role in providing legal protection for both debtors and creditors. The research uses a normative juridical method with a legislative and conceptual approach thru the analysis of Law Number 37 of 2004 concerning Bankruptcy and PKPU, Law Number 18 of 2003 concerning Advocates, the Civil Code, as well as various regulations related to the resolution of commercial disputes. The research results show that lawyers hold a strategic position not only as legal representatives in Commercial Courts but also as legal advisors, negotiators, and debt restructuring facilitators who play a role in maintaining the balance of legal protection for the parties involved. The optimization of the role of lawyers is necessary thru the strengthening of professionalism, integrity, business competence, and a business rescue approach so that the PKPU and bankruptcy processes are not misused as tools of business pressure, but rather become means of fair, effective, and legally certain commercial dispute resolution.